PENERAPAN METODE LITERACY-RICH INSTRUCTION DALAM MENINGKATKAN KEMAMPUAN LITERASI AWAL ANAK USIA DINI DI TKS MAYANG WANGI - Hartitin; Agus Salam; Syahru Ramadhan (STKIP Subang, 2026)
This study was motivated by the low level of early literacy skills among young children at TKS Mayang Wangi, as evidenced by the large number of children who still struggle to recognize letters, identify letter sounds, understand simple vocabulary, and retell the content of stories they have heard. These conditions highlight the need to implement learning strategies that can optimally stimulate literacy through a learning environment rich in language experiences. This study aims to describe and analyze the application of the Literacy-Rich Instruction method in improving early literacy skills among young children at TKS Mayang Wangi. The research method used is Classroom Action Research (CAR) based on the Kemmis and McTaggart model, conducted in two cycles, encompassing the planning, implementation, observation, and reflection stages. The research subjects were 20 children in Group B at TKS Mayang Wangi. Data collection techniques included observation, interviews, documentation, and assessments of the children’s early literacy development. The research results indicate an improvement in children’s early literacy skills in each cycle. In the pre-intervention phase, only 35% (7 children) fell into the “Developing as Expected” (BSH) category. Following the intervention in Cycle I, the percentage increased to 60% (12 children), and in Cycle II it reached 85% (17 children). Additionally, children’s active participation in literacy activities increased from 50% in the pre-intervention phase to 90% in Cycle II. The research findings indicate that the implementation of the Literacy-Rich Instruction method is effective in enhancing early literacy skills among young children through the provision of a literacy-rich environment, the use of diverse media, and interactive reading and storytelling activities.